PEMETAAN KEMISKINAN DI KABUPATEN KEPAHIANG TAHUN 2012 - Rahmat Al Hidayat (JURNAL AGHNIYA, 2019)
This study aims to map poverty that occurs between sub-districts in Kepahiang Regency, to identify poverty reduction programs in Kepahiang Regency. The data used in this research is secondary data obtained from related agencies in Kepahiang Regency in 2012 using descriptive statistical methods. The results of the analysis using the descriptive statistical method, it can be concluded that the area with the highest poverty according to occupation is in Bermani Ilir District, as many as 94.9% of families work as farmers; The regions with the highest poverty according to the number of school facilities are in Seberang Musi District with as many as 12 schools, consisting of 1 Kindergarten, 8 Elementary Schools, 2 Junior High Schools, 1 Senior High School; The regions with the highest poverty according to the number of students are in Seberang Musi District with a total of 1,215 students, consisting of 30 kindergarten students, 884 elementary school students, 220 junior high school students, 81 high school students; The areas with the highest poverty according to health are in Kepahiang District with 431 poor families being referred. Infectious diseases that were handled were 188 cases; The area with the highest poverty according to residence is Seberang Musi District, consisting of 60.1% of the population using electricity, 70% of users of their own toilets, while users of PDAM facilities and garbage dumps do not yet exist; Poverty alleviation programs in Kepahiang District that have been implemented in 2012, namely the cheap rice program, the PNPM program, the KUR program, the Elementary School Poor Student Assistance program, the SLTP Poor Student Assistance program, the SLTA Poor Student Assistance program, the Higher Education Poor Student Assistance program , the Jamkesmas program, the Jamkesda program, and the Jampersal program. Keywords: Poverty, employment, education, health, shelter, prevention program.